Characters’ Speeches as a Plot-Forming Technique in Chronicle “Deviant” Texts - Olga A. Tufanova (Studia Litterarum)
The article examines one of the early chronicle plots, which is based on a conflict of perception of situations and actions, leading to deviant behavior and criminal acts. Using the example of the plot about gathering tribute from the Drevlyans by Prince Igor in the Tale of Bygone Years, the article shows that one of the distinctive features of the texts of this group is the absence of a direct assessment, and the plot lines developed or outlined in them are built on obvious or hidden conflicts of perception by the opposing parties of situation. The characters’ speeches play a significant role in the formation of this plot. In most cases, they represent collective prescriptive speech acts with a typical non-verbal reaction of the characters to whom they were addressed, and a perlocutionary effect, which finds expression in the implementation of verbal appeals by specific actions. A comparison of the original plot with its versions in other chronicle collections shows that in some cases the scribes completely reproduce the text from the Tale of Bygone Years (Lviv Chronicle), while others change historically significant details, still generally preserving the plot outline (Ustyug Chronicle in the copy of L.S. Matsievich, Arkhangelsk Chronicle), and others transform the plot into a short annual record (Vologda Chronicle, Rogozhsky Chronicle). The plot transforms most noticeably in the Book of Degrees, in which the originally hermeneutic narrative simplifies to an ordinary crime plot, common in Russian history. Collective prescriptive speech acts play a significant role in this simplification and plot transformation.